ANALYSIS OF THE ISLAMIC FINANCIAL INSTRUMENTS MARKET - Adkhamjanov Shokhbozbek Bobirjon ugli (American Journals, 2025)
This scientific article comprehensively analyzes the importance of Islamic finance's main financial instruments corresponding to Islamic finance - sukuk - in the modern global financial system. The study carefully studied the international experience gained in the process of using these instruments not only in Muslim countries, but also in the global financial markets.
Keywords: Sukuk, Islamic finance, Islamic financial instruments, Islamic financial funds, Islamic bank.